2014
DOI: 10.1140/epjc/s10052-014-3213-8
|View full text |Cite
|
Sign up to set email alerts
|

Search of wormholes in different dimensional non-commutative inspired space-times with Lorentzian distribution

Abstract: In this paper we ask whether the wormhole solutions exist in different dimensional noncommutativityinspired spacetimes. It is well known that the noncommutativity of the space is an outcome of string theory and it replaced the usual point-like object by a smeared object. Here we have chosen the Lorentzian distribution as the density function in the noncommutativity-inspired spacetime. We have observed that the wormhole solutions exist only in four and five dimensions; however, in higher than five dimensions no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Bhar and Rahaman [27] examined in GR whether the wormhole solutions exist in different dimensional noncommutative space-time with Lorentzian distribution. They found that wormhole solutions appear only for four and five dimensions but no solution exists for higher dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bhar and Rahaman [27] examined in GR whether the wormhole solutions exist in different dimensional noncommutative space-time with Lorentzian distribution. They found that wormhole solutions appear only for four and five dimensions but no solution exists for higher dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Using (14), (15), and (27) in (26), we achieve a complicated differential equation in terms of ( ) that cannot be handled analytically. So, we solve it numerically by choosing the corresponding parameters as 1 = 81, 2 = −0.0091, 3 = 12, and 4 = 32.…”
Section: First Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The slope of b(r ) is positive up to r = 10.45, from which one concludes that the wormhole cannot be arbitrarily large. The same situation occurred in a previous work [37]. Moreover, we consider the energy conditions and the violation of the null energy condition (NEC) i.e., ρ + p r < 0, which is a necessary property for a static wormhole to exist.…”
Section: Solution For Phantom Wormhole and Physical Analysismentioning
confidence: 92%